The impact of non-motor symptoms on the health-related quality of life in patients with functional movement disorders - Věchetová, Gabriela; Slovák, Matěj; Kemlink, David; Hanzlíková, Zuzana; Dušek, Pavel; Nikolai, Tomáš; Růžička, Evžen; Edwards, Mark J; Serranová, Tereza (Journal of psychosomatic research, 2018)
OBJECTIVE: Pain, fatigue, cognitive complaints and psychiatric comorbidities are common in patients with functional movement disorder and may significantly affect their quality of life. The aim of the study was to assess the impact of motor and non-motor symptoms on health-related quality of life in patients with functional movement disorder. METHODS: Sixty-one patients with clinically established functional movement disorder and 61 matched healthy controls completed standardized questionnaires for depression, anxiety, cognitive complaints, fatigue, pain, sleepiness, apathy and health-related quality of life. Motor disorder severity was assessed using The Simplified Functional Movement Disorders Rating Scale. Personality traits were assessed using the 44-Item Big Five Inventory. RESULTS: Compared to controls, patients reported significantly lower health-related quality of life and higher levels of all assessed non-motor symptoms except for apathy. No difference was found in personality traits. In both groups, health-related quality of life scores negatively correlated with depression, anxiety, pain, cognitive complaints, apathy, and neuroticism. No correlation was found between health-related quality of life and motor symptom severity in patients with functional movement disorder. Multiple regression analysis of the predictors of health-related quality of life showed significant impact of trait anxiety and cognitive complaints scores. CONCLUSIONS: Multiple non-motor symptoms but not motor symptom severity correlated with impaired health-related quality of life in patients with functional movement disorder. Impaired health-related quality of life was predicted by anxiety and cognitive complaints. Our results highlight the importance of assessing and treating both motor and non-motor symptoms in patients with functional movement disorder.
Keywords: Non-motor symptoms; pohybové poruchy; Movement Disorders; Functional movement disorder; Humans; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; Health-related quality of life; Personality traits; kvalita života; Quality of Life